A conceptual model of new health service development process: a value-based healthcare view - Mohammadkazemi, Reza; Arzideh, Salar; Ahmadpour Daryani, Mahmoud (Researcher Bulletin of Medical Sciences, 2025)
Objective: The healthcare industry is increasingly exacerbated by costs and demands for quality care, creating opportunities to develop service models that can meet this challenge. Value-based healthcare (VBHC) is one of the emerging solutions for simultaneously considering cost and quality.This study was designed to develop a conceptual model for developing new health services utilizing a VBHC approach to health care. Materials and Methods: A qualitative methodology was utilized, and semi-structured interviews were conducted with 24 project managers from healthcare organizations. Thematic analysis was then conducted on interviews utilizing MAXQDA software; Reliability was ensured through intercoder agreement (ICA = 0.71) and two-case model testing, with independent coding and conflict resolution by a third coder. Results: The thematic analysis resulted in 964 coded segments, which were categorized into seven themes: Innovation Evaluation, Innovation Process, Innovation Technology, Innovation Culture, Customer Value, Interactive Interface, and Customer Participation. The primary findings highlighted the importance of acquiring cost-effective new services that enhance customer value, promoting an innovative culture within the organization, utilizing high technology, and actively engaging with patients and referring physicians through a patient-centric approach. Conclusion: The conceptual model provides an initial guide for healthcare organizations to create new services based on VBHC principles. This model simultaneously addresses cost efficiency, technology-oriented innovation, and patient participation in producing health services aligned with patient improvement per cost. Future research can test and validate this model to context and application within a healthcare setting to better understand its usefulness in helping organizations implement more VBHC services.